Synthesis and characterzation of carbon nanotube and graphenated carbon nanotube superfibre via floating catalyst chemical vapour deposition method - Ibrahim, Nur Izzaiti (2020)
The objective of this research is to develop carbon nanotubes (CNTs) sheet superfibre materials with comparable or exceed properties of existing ones. Superfibres is formed by synthesizing long CNTs using direct-spinning method in horizontal furnace and make them into sheet form. Presently, the superfibres has modest properties but potentially to be strongest fiber known and commonly synthesized using arrays of aligned CNTs and limited studies using direct-spinning method. The interest of producing CNT sheet superfibres is due to no ready industrial format of macroscopic CNTs, since individual CNTs cannot grow longer. Hence, one of the proposed methods to overcome this hindrance is to assemble CNTs into continuous fibres as nanotube superfibre material. Many routes to attain this nanotube superfibre material with outstanding properties but mostly through the post-processing method. In this study, macro assembly of CNTs sheet superfibres was achieved directly from floating catalyst chemical vapour deposition process without post-processing methods. Herein, our interest is to synthesis CNTs and graphenated CNTs sheet superfibres and study their properties. The CNT sheets were directly spun from a hot reactor of the horizontal furnace using floating catalyst chemical vapour deposition. To obtain CNT sheets, three main parameters were used as variables which were reaction temperature (from 1050 °C to 1250 °C), injection rate of precursors (1 ml/hr to 20 ml/hr), and gas flow rate of hydrogen gas (200 sccm to 400 sccm). The spinnability of CNT sheets was observed to highly dependable on the gas flow rate of carrier gas followed by other parameters. The morphological characteristics of CNT sheets showed the synthesized CNTs were multi-walled with a diameter of 17 nm to 49 nm. It was also revealed that, high reaction temperature at 1250 °C and low gas flow rate of hydrogen, (200 sccm and 250 sccm) led to the formation of g-CNTs. TGA analysis showed that high decomposition temperature indicated the presence of multi-walled CNT with purity as high as 98%. Furthermore, high degree of graphitization of the CNT sheets increases with increases of temperature. The highest graphitization of CNT sheet was obtained at temperature 1200 °C with a ratio of ID/IG of 0.37. Besides, the bulk conductivities of CNT sheets were measured and found that CNT sheet synthesized at 350 sccm has thighest electrical conductivity due to the highest packing density of CNTs with a value of 10.72 S cm-1. This research is important because it will enable industries to manufacture new fiber materials which will change engineering designs of potential application such as supercapacitor.